The impact of brand equity on students' choice of Business School. - Tan, Karin Szu Ling. (2009)
Brand equity can create associations that can drive market positions, persist over long time periods and be capable of resisting aggressive competitors. The concept of brand equity has been heavily researched in the area of goods; however, its relation to services, particularly educational services, has not been investigated in depth. Therefore our study aims to study the impact of brand equity on a student’s choice of business school in the Singapore context.